ROLE CONFLICT AND WORK-LIFE BALANCE: WHAT IS MATTER? - Setia Rahajeng Saraswati (Insains Institute, 2023)
Gojek is an online service provider that fulfils customers' needssuch as transport to destinations, food delivery, cargo delivery, and more.other services. After the presence of the Gojek application, especially Go-Ride, Gojek drivers havedrivers have increased. The purpose of this study is to examinethe influence of work-family conflict and flexible working hours on Work-Life Balance and job satisfaction of Gojek GoRide drivers in Purwokerto. This variety of research uses quantitative research. The population inThis research is GoRide Gojek drivers in Purwokerto. Purposive method sampling method was used to select 100 respondents who became sample in this study. This research uses a variety of primary data which iscollected through survey methods by distributing questionnaires. The analysis technique used was multiple linear regression analysis. The findings of this study indicate that Work-Life Balance can be negatively and significantly affected by work-family conflict. The influence of positive and significant influence was also found on Work-Life Balance generated by flexible working hours.by flexible working hours. It was found that work-family conflict has anegative and significant influence on job satisfaction. Flexible working hours has a positive and significant influence on job satisfaction. Work-life balance has a positive and significant influence on job satisfaction